Anticholinergic burden in older adult inpatients: patterns from admission to discharge and associations with hospital outcomes. (May 2021) - Herrero-Zazo, Maria; Berry, Rachel; Bines, Emma; Bhattacharya, Debi; Myint, Phyo K.; Keevil, Victoria L.
Background: Anticholinergic medications are associated with adverse outcomes in older adults and should be prescribed cautiously. We describe the Anticholinergic Risk Scale (ARS) scores of older inpatients and associations with outcomes. Methods: We included all emergency, first admissions of adults ⩾65 years old admitted to one hospital over 4 years. Demographics, discharge specialty, dementia/history of cognitive concern, illness acuity and medications were retrieved from electronic records. ARS scores were calculated as the sum of anticholinergic potential for each medication (0 = limited/none; 1 = moderate; 2 = strong and 3 = very strong). We categorised patients based on admission ARS score [ARS = 0 (reference); ARS = 1; ARS = 2; ARS ⩾ 3] and change in ARS score from admission to discharge [admission and discharge ARS = 0 (reference); same; decreased; increased]. We described anticholinergic prescribing patterns by discharge specialty and explored multivariable associations between ARS score categories and mortality using logistic regression [odds ratios (ORs), 95% confidence intervals (CIs)]. Results: From 33, 360 patients, 10, 183 (31%) were prescribed an anticholinergic medication on admission. Mean admission ARS scores were: Cardiology and Stroke = 0.56; General Medicine = 0.78; Geriatric Medicine = 0.83; Other medicine = 0.81; Trauma and Orthopaedics = 0.66; Other Surgery = 0.65. Mean ARS did not increase from admission to discharge in any specialty but reductions varied significantly, from 4.6% (Other Surgery) to 27.7% (Geriatric Medicine) ( p < 0.001). The odds of both 30-day inpatient and 30-day post-discharge mortality increased with admission ARS = 1 (OR = 1.21, 95% CI 1.01–1.44 and OR = 1.44, 1.18–1.74) but not with ARS = 2 or ARS ⩾ 3. The odds of 30-day post-discharge mortality were higher in all ARS change categories, relative to no anticholinergic exposure (same: OR = 1.45, 1.21–1.74, decreased: OR = 1.27, 1.01–1.57, increased: OR = 2.48, 1.98–3.08). Conclusion: The inconsistent dose–response associations with mortality may be due to confounding and measurement error which may be addressed by a prospective trial. Definitive evidence for this prevalent modifiable risk factor is required to support clinician behaviour-change, thus reducing variation in anticholinergic deprescribing by inpatient speciality. Plain language summary: We describe how commonly medicines which block the chemical acetylcholine are prescribed to older adults admitted to hospital as an emergency and explore links between these medicines and death during or soon after hospital admission Backgroud : Medicines which block the chemical acetylcholine are commonly prescribed to treat symptoms such as itch and difficulty sleeping or to treat medical conditions such as depression. However, some studies in older adults have found potential links between these medicines and confusion and falls. Therefore, doctors are recommended to prescribe these drugs cautiously in adults aged 65 years and over. Methods: In our paper we use data collected as part of routine medical care at one university hospital to describe how often these medicines are prescribed in a large sample of older adults admitted to hospital as an emergency. We look at the medicines patients are prescribed on admission to the hospital and also when they are later discharged. Results: We find that these medicines are frequently prescribed. We also find that, in general, patients are prescribed fewer of these potentially harmful medicines on hospital discharge compared with hospital admission. This suggests that clinicians are aware of advice to prescribe acetylcholine blocking medicines cautiously and they are more often stopped in hospital than started. However, we find a lot of variation in practice depending on which hospital specialty was caring for the patient during their inpatient stay. We also find potential links with these medicines and death during the admission or soon after hospital discharge, but these potential links are not always consistent. Conclusion: Further study is needed to fully understand links between medicines that block acetylcholine and late life health. This will be important to reduce variation in prescribing practices.